Assessment of the diversity and dynamics of Plum pox virus and aphid populations in transgenic European plums under Mediterranean conditions - Capote, Nieves; Pérez-Panadés, J.; Monzó, César; Carbonell, Emilio A.; Urbaneja, Alberto; Scorza, Ralph; Ravelonandro, Michel; Cambra, Mariano (2017)
The molecular variability of Plum pox virus (PPV) populations was compared in transgenic European plums (Prunus domestica L.) carrying the coat protein (CP) gene of PPV and non-transgenic plums in an experimental orchard in Valencia, Spain. A major objective of this study was to detect recombination between PPV CP transgene transcripts and infecting PPV RNA. Additionally, we assessed the number and species of PPV aphid vectors that visited transgenic and non-transgenic plum trees. Test trees consisted of five different P. domestica transgenic lines, i.e. the PPV-resistant C5 'HoneySweet' line and the PPV-susceptible C4, C6, PT6 and PT23 lines, and non-transgenic P. domestica and P. salicina Lind trees. No significant difference in the genetic diversity of PPV populations infecting transgenic and conventional plums was detected, in particular no recombinant between transgene transcripts and incoming viral RNA was found at detectable levels. Also, no significant difference was detected in aphid populations, including viruliferous individuals, that visited transgenic and conventional plums. Our data indicate that PPV-CP transgenic European plums exposed to natural PPV infection over an 8 year period caused limited, if any, risk beyond the cultivation of conventional plums under Mediterranean conditions in terms of the emergence of recombinant PPV and diversity of PPV and aphid populations.